Biophysical characteristics of coastal habitat at Geleang island Karimunjawa National Park as a nesting area hawksbill turtle (Eretmochelys imbricata, Linnaeus 1766) - Anggieta, Yayank Dita; Afiati, Norma; Widyorini, Niniek (Acta Aquatica: Aquatic Sciences Journal, 2024)
The hawksbill turtle (E. imbricata) are internationally Critically Endangered as determined by the IUCN. For this reason, action is needed to preserve the sea turtle in the future. The purpose of this study was to determine the bio-physical characteristics of the beach (beach width and slope; pH, temperature, grain size and sand moisture; nest size; nest distance from high tide; beach vegetation and predators) where hawksbill turtles (E. imbricata) lay their eggs on Geleang Island, Karimunjawa National Park. Concerning conservation, the number, condition, egg removal techniques and egg maintenance found on Geleang Island from January to February 2022 were also described. The research was conducted from January to April 2022 using the observation method which includes field observation and primary data collection. The results showed that Geleang Island has a narrow beach width with a gentle slope. The pH of the sand ranges from 6.5 - 7, the average sand temperature variable is around 28ËšC. Sand humidity has a value range of 82% - 90%. Sand grain analysis on Geleang Island, the results of the most retained sediment were found to be on test sieves with a diameter of 250 µm so that it was classified as a type of medium sand. The dominant vegetations are sea pine (Casuarina equisetifolia) and gabusan (Scaevola taccada). No predators of hatchlings were found on Geleang Island. The amount of hawksbill turtle eggs found on Geleang Island from January to February 2022 amounted to 1.981 eggs.Keywords: Characteristic of coastal habitat; hawksbill hatchlings